Pengembangan Pariwisata Gunung Kelud Pasca Erupsi Tahun 2014 (Studi Pada Kawasan Wisata Gunung Kelud Kabupaten Kediri) - Devi, Sthefani Geby Arsita (Jurnal Administrasi Publik, 2015)
Abstract : The Development of Mount Kelud Tourism after Eruption in 2014 (Studi at the Mount Kelud Tourist Area of Kediri Regency) One of the biggest local income sources comes from tourism sectors. It will significantly contribute to build the area. One of the tourism sectors is the natural beauty of Mount Kelud which is located on the border among Kediri, Blitar, and Malang Regency. The natural beauty of Mount Kelud gets so many tourist attentions, not only from the domestic tourist, but also from foreign tourists. The volcanoes, it’s peak 1,731 above the sea which in 2007 formed a 100 m-wide lava dome known as a child of the mountain. The last eruption on February 14th, 2014 has changed the face of Mount Kelud. Lava dome that used to be an attraction has already vanished. Supporting acces is broken, and the entrance to the mountain peak is disconnected. The purpose of this research are to describe and analyze the condition of Mount Kelud tourism in Kediri Regency before an eruption in 2014, to describe and analyze the condition of Mount Kelud tourism in Kediri Regency after an eruption in 2014, to describe and analyze the development of Mount Kelud tourism after an eruption in 2014, to describe and analyze the challenges in the development of Mount Kelud tourism after an eruption in 2014. This research is done by using qualitative descriptive analysis. The Data collection methods used in this research were interview, documentation, and utilization of secondary data as supporting information. The selected research site was Mount Kelud tourism. Based on the results of the research showed that the condition of Mount Kelud tourism before an eruption in 2014, on the top of Mount Kelud there was a lava dome (the child of Mount Kelud), while the facilities and infrastructures were still quite enough. The condition of Mount Kelud tourism after an eruption in 2014, the lava dome that used to be an attraction for tourists has already vanished and replaced with a large hole, facilities and infrastructures that have been built some of which are vanished and enclosed by the volcanic residual soil of eruption in 2014. The developments of Mount Kelud tourism are focused improving facilities and infrastructures in the Pos I, it is according to the recommendations of the Pusat Vulkanologi Mitigasi dan Bencana Geologi (PVMBG) about safety zone at a 30-km radius. The constructions of facilities and infrastructures such as ATV zone, flying fox, and gazebo. Challenges in developing Mount Kelud tourism, namely: eruptive nature of Mount Kelud, ownership of Mount Kelud, poor communication between government and community around the mountain, little tourist destination, human resources of Mount Kelud operator still need to be improved. Keywords: development, region, tourism. Abstrak : Pengembangan Pariwisata Gunung Kelud Pasca Erupsi Tahun 2014 (Studi Pada Kawasan Wisata Gunung Kelud Kabupaten Kediri) Salah satu sumber penerimaan bagi daerah yang terbesar yakni dari sektor pariwisata. Sektor pariwisata secara signifikan akan sedikit-demi sedikit turut membangun daerah. Salah satunya yakni pesona keindahan alam Gunung Kelud yang teletak di perbatasan antara Kabupaten Kediri, Kabupaten Blitar dan Kabupaten Malang. Pesona alam Gunung Kelud menyedot perhatian para wisatawan, tidak hanya bagi wisatawan domestik, namun juga wisatawan mancanegara. Gunung api setinggi 1.731 mdpl yang pada tahun 2007 muncul kubah lava selebar 100 meter yang disebut anak Gunung. Terjadinya erupsi pada 14 Pebruari 2014 lalu telah banyak merubah wajah Gunung Kelud. Kubah lava yang dulu menjadi daya tarik sekarang menjadi sirna. Akses pendukung rusak, akses menuju puncak terputus. Tujuan dari penelitian ini adalah untuk mendeskripsikan dan menganalisis kondisi pariwisata Gunung Kelud di Kabupaten Kediri sebelum terjadi erupsi tahun 2014, untuk mendeskripsikan dan menganalisis kondisi pariwisata Gunung Kelud di Kabupaten Kediri setelah terjadi erupsi tahun 2014, untuk mendeskripsikan dan menganalisis pengembangan pariwisata Gunung Kelud pasca erupsi tahun 2014, untuk mendeskripsikan dan menganalisis tantangan dalam pengembangan pariwisata Gunung Kelud pasca erupsi tahun 2014. Penelitian ini dilakukan dengan menggunakan analisis deskriptif kualitatif. Metode pengumpulan data yang digunakan dalam penelitian ini adalah wawancara, dokumentasi dan pemanfaatan data sekunder sebagai pendukung informasi. Lokasi dan situs penelitian yang dipilih adalah obyek wisata Gunung Kelud. Berdasarkan hasil penelitian menunjukkan bahwa Kondisi pariwisata Gunung Kelud sebelum erupsi 2014 pada puncak kelud terdapat kubah lava(anak Gunung Kelud), sedangkan untuk sarana dan prasarana cukup memadai. Kondisi pariwisata setelah terjadi erupsi 2014 kubah lava yang menjadi daya tarik wisatawan hilang berganti sebuah lubang besar. sarana dan prasarana yang telah dibangun sebagian hilang tertutup material vulkanik sisa erupsi 2014. Pengembangan pariwisata Gunung Kelud difokuskan untuk peningkatan sarana dan prasarana yang difokuskan di Pos I, hal ini sesuai rekomendasi dari pihak Pusat Vulkanologi Mitigasi dan Bencana Geologi (PVMBG) tentang zona aman pada radius diatas 3 km. Pembangunan sarana dan prasarana seperti zona ATV, Flying fox, dan Gazebo. Tantangan dalam pengembangan pariwisata Gunung Kelud meliputi : sifat erupsi Gunung Kelud, hak pemilikan Gunung Kelud, masih kurangnya komunikasi antara pengelola dan masyarakat sekitar, kurangnya destinasi pariwisata di Gunung Kelud, SDM pengelola Gunung Kelud masih perlu ditingkatkan. Kata Kunci : Pengembangan, Kawasan, Pariwisata.